Knowledge donating and hiding as an organizational basis for intersectoral collaboration: a review of the literature - Iriarte-Ahón, Federico (2020)
The present article presents a literature review on the relationship between knowledge donating and hiding strategies as an organizational basis for intersectoral collaboration. The literature finds that sharing or hiding behavior is a question of individual motivation, which can affect the collaboration process among individuals in a public or private organization. An understanding of this motivation can help organizations to transform their management strategies, thus improving internal and inter-organizational collaboration processes. The review identified various strategies— motivational, social, and national cultural—that are considered to influence individual and group creative capacity and, in turn, on social and technological innovation, the creation of competitive advantage within an organization, and the development of social responsibility policies. The results indicate a lack of consensus regarding motivations, as well as a limited depth of knowledge regarding the behavioral strategies involved in knowledge hiding.